A modeling and prediction method for plunge cutting force considering the small displacement of cutting layer. (September 2020) - Li, Junli; Yu, Weiwei; An, Qinglong; Chen, Ming
In the process of plunge milling, the main cutting force is along the axial direction, and usually, the machining system has good axial rigidity, so it can withstand large cutting loads. This characteristic makes plunge milling particularly suitable for high-efficiency rough machining and semi-finishing of difficult-to-cut materials. The cutting force in the plunge milling process is usually large, and when the process parameters are not selected properly, the plunge milling is prone to the back-off phenomenon. In view of the characteristics of large cutting force and high cutting temperature in Inconel 718 plunge milling process, considering the small displacement of the actual tool tip caused by cutting force and cutting vibration, this article establishes a plunge milling force model based on the combination of analytical method and three-dimensional finite element method. The micro-displacement caused by vibration is obtained through dynamic modeling and modal test methods. Combined with the macro-displacement of cuter back-off under the action of the cutting force during the single-tooth run-in and run-out process, the modified cutting layer parameters are obtained, and optimized cutting force of plunge milling is obtained.